Developing Digital Interactive Exploration of Historical Places with Blending BIM and Virtual Reality - Suhari, Ketut Tomy; Purwanto, Hery; Andinisari, Ratri (The Indonesian Journal of Computer Science, 2024)
The advancement of technology has opened new possibilities for exploring and experiencing historical places. This research aims to develop a digital interactive exploration platform that blends BIM and VR to provide an immersive and informative experience of historical sites. The study focuses on Candi Kidal, located in Kecamatan Tumpang, Kabupaten Malang, as the primary study area. The proposed method involves the integration of BIM and VR technologies to create a detailed and interactive virtual representation of Candi Kidal. The BIM models are the foundation for capturing and integrating various data sources. These models are then transformed into a VR environment, allowing users to explore the site virtually, interact with objects, and access relevant historical information. Data collection methods include site surveys, and historical research in the field. The BIM models are developed using software tools such as Autodesk Revit, while the VR environment is created using platforms like Unity3D. The development of the digital interactive exploration platform involves programming and scripting languages such as C#. The results demonstrate the effectiveness of developed platform in providing an immersive and informative experience for Candi Kidal. Users can navigate the virtual environment, view detailed architectural elements, and access historical information through interactive interfaces. The significance of this research lies in its potential to enhance the preservation, promotion, and accessibility of historical places. By blending BIM and VR technologies, the digital interactive exploration platform offers a unique and engaging experience that can attract a wider audience and foster a deeper understanding of cultural heritage.